Integrated preparation method of gradient low-dielectric high-temperature-resistant wave-transmitting material

Through the integrated preparation method of gradient low-dielectric high-temperature wave-resistance material, combined with porous quartz fiber ceramic body and silicon sol solution, the problem of existing materials being difficult to combine high strength, low dielectric constant, low dielectric loss and wide frequency wave-transmitting performance, and efficiently prepare materials with these excellent properties.

CN119613133AActive Publication Date: 2025-03-14SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411528767.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-14
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

Existing high-temperature wave-transmissive materials are difficult to achieve both high strength, low dielectric constant, low dielectric loss and wide frequency wave-transmissive performance.

Method used

A integrated preparation method of gradient low dielectric resistance and high temperature wave-transmissive materials is adopted to prepare a variety of porous quartz fiber ceramic substrates with different porosity and dielectric constants by combining the porous quartz fiber ceramic body with silicon sol solution, and a gradient structure is formed by sintering treatment.

Benefits of technology

The preparation of gradient low-dielectric high-temperature wave-transmissive materials with high strength, low dielectric constant, low dielectric loss and wide frequency wave-transmissive performance is achieved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to an integrated preparation method of a gradient low-dielectric high-temperature-resistant wave-transparent material. The integrated preparation method comprises the following steps: preparing a porous quartz fiber ceramic green body; preparing a plurality of porous quartz fiber ceramic matrixes from the porous quartz fiber ceramic green body by utilizing a plurality of silica sol solutions; the silica sol solution comprises a first silica sol solution to an nth silica sol solution; the porous quartz fiber ceramic matrixes comprise a first porous quartz fiber ceramic matrix to an nth porous quartz fiber ceramic matrix; processing the first porous quartz fiber ceramic matrix to the nth porous quartz fiber ceramic matrix according to corresponding preset sizes to obtain a first porous quartz fiber ceramic sub-piece to an nth porous quartz fiber ceramic sub-piece; fitting, mounting, fixing and sintering the first porous quartz fiber ceramic sub-component to the nth porous quartz fiber ceramic sub-component according to a preset sequence; the gradient low-dielectric high-temperature-resistant wave-transparent material has the advantages of high strength, low dielectric constant, low dielectric loss and broadband wave permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high temperature resistant wave-transmitting materials, and in particular to the technical field of an integrated preparation method for a gradient low dielectric high temperature resistant wave-transmitting material. Background Art

[0002] High temperature resistant and wave-transparent materials are widely used in the aerospace field, and are widely used in key components of radar guidance systems such as radomes, which protect the internal seeker from external high-speed flight aerodynamic thermal ablation and effectively transmit electromagnetic waves, combining heat protection, load bearing and wave-transparent functions. With the continuous improvement of combat requirements such as equipment flight speed, precision guidance, and offensive and defensive confrontation, the development of ceramic radomes with both high temperature resistance and broadband wave-transparent performance has become one of the research hotspots at home and abroad.

[0003] The dielectric constant and dielectric loss of traditional high-temperature resistant wave-transmitting materials are mainly determined by the composition of the raw materials. Therefore, it is difficult to make the dielectric constant and dielectric loss very low, and it is impossible to achieve broadband wave transmission.

[0004] Therefore, how to prepare high-temperature resistant wave-transmitting materials with high strength, low dielectric constant, low dielectric loss and broadband wave-transmitting performance has become a difficult problem that needs to be solved urgently in this field. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide an integrated preparation method of a gradient low-dielectric high-temperature resistant wave-transparent material, so as to achieve high strength, low dielectric constant, low dielectric loss and broadband wave-transparent performance.

[0006] The present invention provides an integrated preparation method of a gradient low-dielectric high-temperature resistant wave-transmitting material, comprising the following steps: preparing a porous quartz fiber ceramic blank;

[0007] Using a porous quartz fiber ceramic body and a plurality of silica sol solutions to prepare a plurality of porous quartz fiber ceramic substrates;

[0008] The silica sol solution includes a first silica sol solution to an nth silica sol solution;

[0009] The porous quartz fiber ceramic matrix includes a first porous quartz fiber ceramic matrix to an nth porous quartz fiber ceramic matrix;

[0010] The porous quartz fiber ceramic body is impregnated with a first silica sol solution, dried, and sintered to prepare a first porous quartz fiber ceramic matrix;

[0011] The second porous quartz fiber ceramic body to the nth porous quartz fiber ceramic substrate are prepared by respectively impregnating, drying and sintering the porous quartz fiber ceramic body with the second silica sol to the nth silica sol;

[0012] Processing the first porous quartz fiber ceramic substrate to the nth porous quartz fiber ceramic substrate according to corresponding preset sizes to obtain the first porous quartz fiber ceramic sub-component to the nth porous quartz fiber ceramic sub-component;

[0013] Adhere ceramic slurry to the surface of the first porous quartz fiber ceramic sub-component and the n-1th porous quartz fiber ceramic sub-component; the ceramic slurry comprises quartz powder, a sintering aid, and alcohol in a mass ratio of (9-11): (1-5): (95-105); the sintering aid comprises boron oxide;

[0014] The first porous quartz fiber ceramic sub-component and the nth porous quartz fiber ceramic sub-component are fitted, fixed, and then sintered to obtain the gradient low-dielectric high-temperature resistant wave-transmitting material; the sintering temperature is 1000°C-1100°C.

[0015] Compared with the prior art, the present invention has the following beneficial effects: the porous quartz fiber ceramic matrix includes the first porous quartz fiber ceramic matrix to the nth porous quartz fiber ceramic matrix, so that a plurality of porous quartz fiber ceramic matrices with different porosities can be prepared, and thus the porous quartz fiber ceramic matrix has different densities, so that a plurality of porous quartz fiber ceramic matrices with different dielectric losses can be prepared;

[0016] The silica sol solutions including the first silica sol solution to the nth silica sol solution are used to prepare a plurality of silica sols with different concentrations;

[0017] The porous quartz fiber ceramic green body is impregnated, dried and sintered by the first silica sol to the nth silica sol respectively to prepare the second porous quartz fiber ceramic green body to the nth porous quartz fiber ceramic matrix, so as to prepare more kinds of porous quartz fiber ceramic sub-components with various dielectric constants, and the dielectric constants of various porous quartz fiber ceramic sub-components are very low;

[0018] The porous quartz fiber ceramic blank is impregnated with silica sol, dried and then sintered. The sintering temperature is low, that is, the debinding is achieved. At the same time, the porous quartz fiber ceramic matrix has a certain strength, and the porous quartz fiber ceramic sub-components can be processed and prepared. At the same time, the prepared porous quartz fiber ceramic sub-components have high activity inside. When the first porous quartz fiber ceramic sub-component to the nth porous quartz fiber ceramic sub-component are fitted, fixed and then sintered in a preset order, the bonding strength of each porous quartz fiber ceramic sub-component is high, and the gradient low dielectric high temperature resistant wave-transmitting material is prepared in an integrated manner, thereby achieving the high strength of the gradient low dielectric high temperature resistant wave-transmitting material;

[0019] Ceramic slurry is attached to the surface of the n-1 porous quartz fiber ceramic sub-component through the first porous quartz fiber ceramic sub-component; the ceramic slurry includes quartz powder, sintering aid, and alcohol in a mass ratio of (9-11): (1-5): (95-105); the sintering aid includes boron oxide, etc., so that the ceramic slurry and the porous quartz fiber ceramic sub-component react chemically during the subsequent sintering process to form borosilicate compounds, so as to achieve high strength and improved high temperature resistance of the gradient low dielectric high temperature resistant wave-transmitting material;

[0020] The prepared gradient low-dielectric high-temperature resistant wave-transmitting material has high strength, low dielectric constant, low dielectric loss and broadband wave-transmitting performance.

[0021] Further, when n=3, the silica sol solution includes a first silica sol solution, a second silica sol solution, and a third silica sol solution;

[0022] The first silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the first silica sol solution is 10-30% and the pH is 4-6;

[0023] The second silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the second silica sol solution is 31-41% and the pH is 4-6;

[0024] The third silica sol solution is obtained by adjusting the pH of silica sol with ammonia water. The silica sol concentration of the third silica sol solution is 41-55%, and the pH is 4-6.

[0025] The beneficial effect of adopting the previous step is that silica sols of different concentrations can be prepared.

[0026] Furthermore, the preparation process of the porous quartz fiber ceramic body comprises the following steps:

[0027] The quartz fiber and the alumina fiber are sheared respectively to obtain short fiber 1 and short fiber 2;

[0028] Mix short fiber 1, short fiber 2, deionized water and additives in a ratio of (50-90): (10-40): (100-200): (10-15), stir and disperse for 60-120 minutes to obtain a quartz fiber ceramic slurry;

[0029] Adding quartz fiber ceramic slurry into a molding mold, and then filtering and molding;

[0030] Then, the product is dried and sintered at high temperature to obtain a porous quartz fiber ceramic body.

[0031] Furthermore, the additive includes boron oxide; the aspect ratio of the short fiber 1 is (100-1000):1, and the aspect ratio of the short fiber 2 is (100-500):1.

[0032] The beneficial effect of the above step is that the aspect ratio of the short fiber 1 is (100-1000):1, the aspect ratio of the short fiber 2 is (100500):1, and the short fiber 1 and the short fiber 2 are mixed in a ratio of (50-90): (10-40) to obtain a porous quartz fiber ceramic blank with different porosities; the short fiber 1, the short fiber 2, deionized water, and the additive are mixed in proportion, and the additive includes boron oxide, so that the boron oxide reacts with the quartz fiber at the fiber intersection inside the porous quartz fiber ceramic blank to form a borosilicate compound, thereby achieving high strength of the quartz fiber ceramic blank after forming, and avoiding the problem of partial material filling the porous quartz fiber ceramic blank and reducing the porosity; thereby achieving the internal porosity of the porous quartz fiber ceramic blank mainly obtained by mixing the short fiber 1 and the short fiber 2 in a ratio of (50-90), thereby achieving the controllable and adjustable internal porosity of the porous quartz fiber ceramic blank.

[0033] Further, the porous quartz fiber ceramic matrix includes a first porous quartz fiber ceramic matrix, a second porous quartz fiber ceramic matrix, and a third porous quartz fiber ceramic matrix;

[0034] The porous quartz fiber ceramic body is placed in a vacuum container for vacuum treatment, the feed port at the bottom of the vacuum container is opened to siphon the first silica sol solution into the vacuum container, and the feed port at the bottom of the vacuum container is closed to continue vacuuming for 30-60 minutes; the porous quartz fiber ceramic body after impregnation is heated together with the container and the first silica sol solution, and the first silica sol solution is gelled; the porous quartz fiber ceramic body after gelation is dried at a drying temperature of (100-150)°C, and then high-temperature calcined at a calcination temperature of (600-800)°C to obtain a first porous quartz fiber ceramic matrix; the first silica sol solution is heated to a gelling temperature of (80-100)°C;

[0035] The porous quartz fiber ceramic body is placed in a vacuum container for vacuum treatment, the feed port at the bottom of the vacuum container is opened to siphon the second silica sol solution into the vacuum container, and the feed port at the bottom of the vacuum container is closed to continue vacuuming for 30-60 minutes; the porous quartz fiber ceramic body after impregnation is heated together with the container and the second silica sol solution, and the second silica sol solution is gelled; the porous quartz fiber ceramic body after gelation is dried at a drying temperature of (100-150)°C, and then high-temperature calcined at a calcination temperature of (600-800)°C, and then high-temperature calcined to obtain a second porous quartz fiber ceramic matrix;

[0036] The second silica sol solution is heated to a gel temperature of (80-100)°C;

[0037] The porous quartz fiber ceramic body is placed in a vacuum container for vacuum treatment, the feed port at the bottom of the vacuum container is opened to siphon the third silica sol solution into the vacuum container, and the feed port at the bottom of the vacuum container is closed to continue vacuuming for 30-60 minutes; the porous quartz fiber ceramic body after impregnation is heated together with the container and the third silica sol solution, and the third silica sol solution is silica sol gelled; the porous quartz fiber ceramic body after gelling is dried at a drying temperature of (100-150)°C, and then high-temperature calcined at a calcination temperature of (600-800)°C, and then high-temperature calcined to obtain a third porous quartz fiber ceramic matrix;

[0038] The third silica sol solution is heated to a gel temperature of (80-100)°C.

[0039] The beneficial effect of the previous step is that the porous quartz fiber ceramic body is uniformly impregnated with the silica sol solution to obtain a porous quartz fiber ceramic matrix; the porous quartz fiber ceramic body after gelation is dried at a temperature of (100-150)°C, and then calcined at a high temperature of (600-800)°C, so that the porous quartz fiber ceramic matrix has a certain strength for cutting and processing, and the internal organic matter has been volatilized, but the internal chemical activity is beneficial to the subsequent overall sintering, and the adjacent porous quartz fiber ceramic sub-components have a high strength.

[0040] Further, the first porous quartz fiber ceramic substrate, the third porous quartz fiber ceramic substrate, and the third porous quartz fiber ceramic substrate are processed according to corresponding preset sizes to obtain a first porous quartz fiber ceramic sub-component, a second porous quartz fiber ceramic sub-component, and a third porous quartz fiber ceramic sub-component;

[0041] The first porous quartz fiber ceramic sub-component has a thickness of 5-10 mm and a dielectric constant of 1.3-1.5; the second porous quartz fiber ceramic sub-component has a thickness of 30-40 mm and a dielectric constant of 1.5-1.6; the third porous quartz fiber ceramic sub-component has a thickness of 10-20 mm and a dielectric constant of 1.8-1.9;

[0042] Preferably, the dielectric loss of the first porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, and the third porous quartz fiber ceramic sub-component are all (1-5)×10 -3

[0043] Further, the porous quartz fiber ceramic body includes a first porous quartz fiber ceramic body, a second porous quartz fiber ceramic body, and a third porous quartz fiber ceramic body;

[0044] The ratio of short fiber 1, short fiber 2, deionized water and additives in the first porous quartz fiber ceramic body is (70-90): (10-20): (100-200): (10-15);

[0045] The density of the first porous quartz fiber ceramic body is 0.297-0.505 g / cm 3 ;

[0046] The ratio of short fiber 1, short fiber 2, deionized water and additive in the second porous quartz fiber ceramic body is (60-80): (20-30): (100-200): (10-15);

[0047] The density of the second porous quartz fiber ceramic body is 0.595-0.65 g / cm 3 ;

[0048] The ratio of short fiber 1, short fiber 2, deionized water and additives in the third porous quartz fiber ceramic body is (50-70): (30-40): (100-200): (10-15);

[0049] The density of the third porous quartz fiber ceramic body is 0.81-0.95 g / cm 3 ;

[0050] Preferably, the dielectric loss of the first porous quartz fiber ceramic body, the second porous quartz fiber ceramic body, and the third porous quartz fiber ceramic body are all (1-3)×10 -3 .

[0051] The beneficial effect of the above step is that the porous quartz fiber ceramic body with a preset porosity is prepared by mixing the short fibers 1 and the short fibers 2 in different mass ratios and adding additives, thereby obtaining a preset dielectric constant. By combining different dielectric constants and corresponding porous quartz fiber ceramic body thicknesses with filling of silica sols with different concentrations, a low dielectric loss is achieved, and the dielectric loss is less than (1-5)×10 -3 ; Thereby achieving a gradient low dielectric high temperature resistant wave-transmitting material having low dielectric constant, low dielectric loss and broadband wave-transmitting performance.

[0052] Furthermore, the first porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, and the third porous quartz fiber ceramic sub-component are all arranged horizontally, and then the third porous quartz fiber ceramic sub-component, the first porous quartz fiber ceramic sub-component, and the second porous quartz fiber ceramic sub-component are sequentially bonded, connected, and fixed, and then sintered to obtain the gradient low-dielectric high-temperature resistant wave-transmitting material.

[0053] The beneficial effect of adopting the previous step is that the porous quartz fiber ceramic sub-components are all arranged horizontally, and the dielectric constant of the first porous quartz fiber ceramic sub-component located in the middle is the lowest, the dielectric constants of the second porous quartz fiber ceramic sub-component and the third porous quartz fiber ceramic sub-component located on both sides are higher than the dielectric constants of the first porous quartz fiber ceramic sub-component, and the thickness of the first porous quartz fiber ceramic sub-component is the lowest, thereby achieving broadband wave transmission with low dielectric loss.

[0054] Furthermore, when n=4, the silica sol solution includes a first silica sol solution, a second silica sol solution, a third silica sol solution, and a fourth silica sol solution;

[0055] The first silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the first silica sol solution is 0-20% and the pH is 4-6;

[0056] The second silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the second silica sol solution is 21-35%, and the pH is 4-6;

[0057] The third silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the third silica sol solution is 36-45%, and the pH is 4-6;

[0058] The fourth silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the fourth silica sol solution is 41-55%, and the pH is 4-6;

[0059] and / or

[0060] The porous quartz fiber ceramic body includes a first porous quartz fiber ceramic body, a second porous quartz fiber ceramic body, a third porous quartz fiber ceramic body, and a fourth porous quartz fiber ceramic body;

[0061] The ratio of short fiber 1, short fiber 2, deionized water and additives in the first porous quartz fiber ceramic body is (80-90): (10-15): (100-200): (10-15);

[0062] The density of the first porous quartz fiber ceramic body is 0.27-0.45 g / cm 3 ;

[0063] The ratio of short fiber 1, short fiber 2, deionized water and additive in the second porous quartz fiber ceramic body is (70-80): (15-25): (100-200): (10-15);

[0064] The density of the second porous quartz fiber ceramic body is 0.45-0.65 g / cm 3;

[0065] The ratio of short fiber 1, short fiber 2, deionized water and additives in the third porous quartz fiber ceramic body is (60-70): (20-30): (100-200): (10-15);

[0066] The density of the third porous quartz fiber ceramic body is 0.7-0.9 g / cm 3 ;

[0067] The ratio of short fiber 1, short fiber 2, deionized water and additives in the fourth porous quartz fiber ceramic body is (50-60): (30-40): (100-200): (10-15);

[0068] The density of the fourth porous quartz fiber ceramic body is 0.85-0.95 g / cm 3 ;

[0069] Preferably, the dielectric loss of the first porous quartz fiber ceramic body, the second porous quartz fiber ceramic body, the third porous quartz fiber ceramic body, and the fourth porous quartz fiber ceramic body are all (1-3)×10 -3 ;

[0070] Preferably, the dielectric loss of the first porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, the third porous quartz fiber ceramic sub-component, and the fourth porous quartz fiber ceramic sub-component are all (1-5)×10 -3 .

[0071] The beneficial effect of adopting the previous step is that four porous quartz fiber ceramic bodies with different densities are prepared according to a preset plan, thereby preparing porous quartz fiber ceramic bodies with preset different dielectric constants; porous quartz fiber ceramic bodies with different thicknesses are impregnated with silica sol solutions of different concentrations to achieve an overall gradient low dielectric high temperature resistant wave-transmitting material with broadband wave transmission and reduced dielectric loss.

[0072] Further, the first porous quartz fiber ceramic substrate, the third porous quartz fiber ceramic substrate, the third porous quartz fiber ceramic substrate, and the fourth porous quartz fiber ceramic substrate are respectively processed according to corresponding preset sizes to obtain a first porous quartz fiber ceramic sub-component, a second porous quartz fiber ceramic sub-component, a third porous quartz fiber ceramic sub-component, and a fourth porous quartz fiber ceramic sub-component;

[0073] The first porous quartz fiber ceramic sub-component has a thickness of 45-50 mm and a dielectric constant of 1.3-1.4; the second porous quartz fiber ceramic sub-component has a thickness of 35-40 mm and a dielectric constant of 1.5-1.6; the third porous quartz fiber ceramic sub-component has a thickness of 25-30 mm and a dielectric constant of 1.7-1.8; the fourth porous quartz fiber ceramic sub-component has a thickness of 40-45 mm and a dielectric constant of 1.8-1.9;

[0074] The first porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, and the third porous quartz fiber ceramic sub-component are all bent, and then the fourth porous quartz fiber ceramic sub-component, the third porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, and the first porous quartz fiber ceramic sub-component are sequentially bonded, connected, and fixed, and then sintered to obtain the gradient low-dielectric high-temperature resistant wave-transmitting material.

[0075] The beneficial effect of adopting the previous step is that the dielectric constants of the first porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, the third porous quartz fiber ceramic sub-component, and the fourth porous quartz fiber ceramic sub-component connected in sequence are reduced in sequence, but the thickness is first reduced and then reduced, which more effectively improves the broadband wave transmission performance of the gradient low dielectric high temperature resistant wave transparent material, while avoiding the problem of increased dielectric loss caused by an increase in the number of layers, thereby achieving still low dielectric loss.

[0076] The first porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, and the third porous quartz fiber ceramic sub-component are all bent, which is further beneficial to improving the broadband wave transmission performance and achieving an effective wave focusing effect, thereby improving the wave transmission strength and avoiding the problem of reduced wave transmission strength due to an increase in the number of layers; and at the same time, the strength of the gradient low dielectric high temperature resistant wave transmission material is increased. DETAILED DESCRIPTION

[0077] In order to better understand the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments.

[0078] Embodiment 1

[0079] This embodiment provides an integrated preparation method of a gradient low-dielectric high-temperature resistant wave-transmitting material, comprising the following steps: preparing a porous quartz fiber ceramic body;

[0080] The preparation process of the porous quartz fiber ceramic body comprises the following steps:

[0081] The quartz fiber and the alumina fiber are sheared respectively to obtain short fiber 1 and short fiber 2;

[0082] The short fiber 1, short fiber 2, deionized water and additives were mixed in a ratio of 70:25:150:13, stirred and dispersed for 90 minutes to obtain a quartz fiber ceramic slurry;

[0083] The quartz fiber ceramic slurry is added into a forming mold, and then filtered to form; and then dried and sintered at a high temperature to obtain a porous quartz fiber ceramic body.

[0084] The additive includes boron oxide; the length-to-diameter ratio of the short fiber 1 is 550:1, and the length-to-diameter ratio of the short fiber 2 is 300:1.

[0085] The porous quartz fiber ceramic body includes a first porous quartz fiber ceramic body, a second porous quartz fiber ceramic body, and a third porous quartz fiber ceramic body;

[0086] The ratio of short fiber 1, short fiber 2, deionized water and additive in the first porous quartz fiber ceramic body is 80:15:150:13;

[0087] The density of the first porous quartz fiber ceramic body is 0.4 g / cm 3 ;

[0088] The ratio of short fiber 1, short fiber 2, deionized water and additive in the second porous quartz fiber ceramic body is 70:25:150:13;

[0089] The density of the second porous quartz fiber ceramic body is 0.62 g / cm 3 ;

[0090] The ratio of short fiber 1, short fiber 2, deionized water and additive in the third porous quartz fiber ceramic body is 60:35:150:13;

[0091] The density of the third porous quartz fiber ceramic body is 0.88 g / cm 3 ;

[0092] Preferably, the dielectric loss of the first porous quartz fiber ceramic body, the second porous quartz fiber ceramic body, and the third porous quartz fiber ceramic body is (1.8-2.2)×10 -3 ;

[0093] Using a porous quartz fiber ceramic body and a plurality of silica sol solutions to prepare a plurality of porous quartz fiber ceramic substrates;

[0094] The silica sol solution includes a first silica sol solution to a third silica sol solution;

[0095] The porous quartz fiber ceramic matrix includes a first porous quartz fiber ceramic matrix to an nth porous quartz fiber ceramic matrix;

[0096] The porous quartz fiber ceramic body is impregnated with a first silica sol solution, dried, and sintered to prepare a first porous quartz fiber ceramic matrix;

[0097] The second silica sol to the third silica sol are used to impregnate, dry and sinter the porous quartz fiber ceramic body to prepare the second porous quartz fiber ceramic body to the third porous quartz fiber ceramic matrix;

[0098] The silica sol solution includes a first silica sol solution, a second silica sol solution, and a third silica sol solution;

[0099] The first silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the first silica sol solution is 20% and the pH is 5;

[0100] The second silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the second silica sol solution is 36% and the pH is 5;

[0101] The third silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the third silica sol solution is 48% and the pH is 5;

[0102] Processing the first porous quartz fiber ceramic substrate to the third porous quartz fiber ceramic substrate according to corresponding preset sizes to obtain the first porous quartz fiber ceramic sub-component to the third porous quartz fiber ceramic sub-component;

[0103] The porous quartz fiber ceramic matrix includes a first porous quartz fiber ceramic matrix, a second porous quartz fiber ceramic matrix, and a third porous quartz fiber ceramic matrix;

[0104] The porous quartz fiber ceramic body is placed in a vacuum container for vacuum treatment, the feed port at the bottom of the vacuum container is opened to siphon the first silica sol solution into the vacuum container, and the feed port at the bottom of the vacuum container is closed to continue vacuuming for 45 minutes; the porous quartz fiber ceramic body after impregnation is heated together with the container and the first silica sol solution, and the first silica sol solution is gelled; the porous quartz fiber ceramic body after gelation is dried at a drying temperature of 125°C, and then high-temperature calcined at a calcination temperature of 700°C to obtain a first porous quartz fiber ceramic matrix; the first silica sol solution is heated to a gelling temperature of 90°C;

[0105] The porous quartz fiber ceramic body is placed in a vacuum container for vacuum treatment, the feed port at the bottom of the vacuum container is opened to siphon the second silica sol solution into the vacuum container, and the feed port at the bottom of the vacuum container is closed to continue vacuuming for 45 minutes; the porous quartz fiber ceramic body after impregnation is heated together with the container and the second silica sol solution, and the second silica sol solution is gelled; the porous quartz fiber ceramic body after gelation is dried at a drying temperature of 125°C, and then high-temperature calcined at a calcination temperature of 700°C, and then high-temperature calcined to obtain a second porous quartz fiber ceramic matrix;

[0106] The second silica sol solution is heated to a gel temperature of 90°C;

[0107] The porous quartz fiber ceramic body is placed in a vacuum container for vacuum treatment, the feed port at the bottom of the vacuum container is opened to siphon the third silica sol solution into the vacuum container, and the feed port at the bottom of the vacuum container is closed to continue vacuuming for 45 minutes; the porous quartz fiber ceramic body after impregnation is heated together with the container and the third silica sol solution, and the third silica sol solution is silica sol gelled; the porous quartz fiber ceramic body after gelling is dried at a drying temperature of 125°C, and then high-temperature calcined at a calcination temperature of 700°C, and then high-temperature calcined to obtain a third porous quartz fiber ceramic matrix;

[0108] The third silica sol solution is heated to a gel temperature of 90°C.

[0109] The first porous quartz fiber ceramic substrate, the third porous quartz fiber ceramic substrate, and the third porous quartz fiber ceramic substrate are processed according to corresponding preset sizes to obtain a first porous quartz fiber ceramic sub-component, a second porous quartz fiber ceramic sub-component, and a third porous quartz fiber ceramic sub-component;

[0110] The first porous quartz fiber ceramic sub-component has a thickness of 8 mm and a dielectric constant of 1.4; the second porous quartz fiber ceramic sub-component has a thickness of 35 mm and a dielectric constant of 1.55; the third porous quartz fiber ceramic sub-component has a thickness of 15 mm and a dielectric constant of 1.85;

[0111] The dielectric loss of the first porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, and the third porous quartz fiber ceramic sub-component is (2.8-3.2)×10 -3 .

[0112] Attaching ceramic slurry to the surface of the first porous quartz fiber ceramic sub-component and the second porous quartz fiber ceramic sub-component; the ceramic slurry includes quartz powder, sintering aid, and alcohol in a mass ratio of 10:3:100; the sintering aid includes boron oxide;

[0113] The first porous quartz fiber ceramic sub-component and the third porous quartz fiber ceramic sub-component are fitted, fixed, and then sintered to obtain the gradient low-dielectric high-temperature resistant wave-transmitting material; the sintering temperature is 1050° C.;

[0114] The first porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, and the third porous quartz fiber ceramic sub-component are all arranged horizontally, and then the third porous quartz fiber ceramic sub-component, the first porous quartz fiber ceramic sub-component, and the second porous quartz fiber ceramic sub-component are sequentially bonded, connected, and fixed, and then sintered to obtain the gradient low-dielectric high-temperature resistant wave-transmitting material.

[0115] Embodiment 2

[0116] The features of this embodiment that are the same as those of the first embodiment are not described in detail. The features of this embodiment that are different from those of the first embodiment are as follows: This embodiment provides an integrated preparation method for a gradient low-dielectric high-temperature resistant wave-transmitting material, comprising the following steps, wherein the silica sol solution comprises a first silica sol solution, a second silica sol solution, a third silica sol solution, and a fourth silica sol solution;

[0117] The first silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the first silica sol solution is 18% and the pH is 5.8;

[0118] The second silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the second silica sol solution is 33% and the pH is 5.8;

[0119] The third silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the third silica sol solution is 43% and the pH is 5.8;

[0120] The fourth silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the third silica sol solution is 53% and the pH is 4.8;

[0121] The porous quartz fiber ceramic body includes a first porous quartz fiber ceramic body, a second porous quartz fiber ceramic body, a third porous quartz fiber ceramic body, and a fourth porous quartz fiber ceramic body;

[0122] The ratio of short fiber 1, short fiber 2, deionized water and additive in the first porous quartz fiber ceramic body is 88:13:180:14;

[0123] The density of the first porous quartz fiber ceramic body is 0.43 g / cm 3 ;

[0124] The ratio of short fiber 1, short fiber 2, deionized water and additive in the second porous quartz fiber ceramic body is 73:23:180:13;

[0125] The density of the second porous quartz fiber ceramic body is 0.55 g / cm 3 ;

[0126] The ratio of short fiber 1, short fiber 2, deionized water and additive in the third porous quartz fiber ceramic body is 63:28:180:13;

[0127] The density of the third porous quartz fiber ceramic body is 0.8 g / cm 3 ;

[0128] The ratio of short fiber 1, short fiber 2, deionized water and additive in the fourth porous quartz fiber ceramic body is 53:38:180:13;

[0129] The density of the fourth porous quartz fiber ceramic body is 0.93 g / cm 3 ;

[0130] The dielectric loss of the first porous quartz fiber ceramic body, the second porous quartz fiber ceramic body, the third porous quartz fiber ceramic body, and the fourth porous quartz fiber ceramic body is (1.8-2.2)×10 -3 ;

[0131] The dielectric loss of the first porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, the third porous quartz fiber ceramic sub-component, and the fourth porous quartz fiber ceramic sub-component is (2.8-3.3)×10 -3 .

[0132] The first porous quartz fiber ceramic substrate, the third porous quartz fiber ceramic substrate, the third porous quartz fiber ceramic substrate, and the fourth porous quartz fiber ceramic substrate are processed according to corresponding preset sizes to obtain a first porous quartz fiber ceramic sub-component, a second porous quartz fiber ceramic sub-component, a third porous quartz fiber ceramic sub-component, and a fourth porous quartz fiber ceramic sub-component;

[0133] The first porous quartz fiber ceramic sub-component has a thickness of 46 mm and a dielectric constant of 1.32; the second porous quartz fiber ceramic sub-component has a thickness of 36 mm and a dielectric constant of 1.52; the third porous quartz fiber ceramic sub-component has a thickness of 26 mm and a dielectric constant of 1.72; the fourth porous quartz fiber ceramic sub-component has a thickness of 41 mm and a dielectric constant of 1.82;

[0134] The first porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, and the third porous quartz fiber ceramic sub-component are all bent, and then the fourth porous quartz fiber ceramic sub-component, the third porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, and the first porous quartz fiber ceramic sub-component are sequentially bonded, connected, and fixed, and then sintered to obtain the gradient low-dielectric high-temperature resistant wave-transmitting material.

[0135] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the present application.

Claims

1. A method for preparing an integrated gradient low dielectric high temperature resistant wave-transmitting material, characterized in that: The following steps are involved: preparing a porous quartz fiber ceramic body; Using a porous quartz fiber ceramic body and a plurality of silica sol solutions to prepare a plurality of porous quartz fiber ceramic substrates; The silica sol solution includes a first silica sol solution to an nth silica sol solution; The porous quartz fiber ceramic matrix includes a first porous quartz fiber ceramic matrix to an nth porous quartz fiber ceramic matrix; The porous quartz fiber ceramic body is impregnated with a first silica sol solution, dried, and sintered to prepare a first porous quartz fiber ceramic matrix; The second porous quartz fiber ceramic body to the nth porous quartz fiber ceramic substrate are prepared by respectively impregnating, drying and sintering the porous quartz fiber ceramic body with the second silica sol to the nth silica sol; Processing the first porous quartz fiber ceramic substrate to the nth porous quartz fiber ceramic substrate according to corresponding preset sizes to obtain the first porous quartz fiber ceramic sub-component to the nth porous quartz fiber ceramic sub-component; Adhere ceramic slurry to the surface of the first porous quartz fiber ceramic sub-component and the n-1th porous quartz fiber ceramic sub-component; the ceramic slurry comprises quartz powder, a sintering aid, and alcohol in a mass ratio of (9-11): (1-5): (95-105); the sintering aid comprises boron oxide; The first porous quartz fiber ceramic sub-component and the nth porous quartz fiber ceramic sub-component are fitted, fixed, and then sintered to obtain the gradient low-dielectric high-temperature resistant wave-transmitting material; the sintering temperature is 1000°C-1100°C.

2. The integrated preparation method of gradient low dielectric high temperature resistant wave-transmitting material according to claim 1 is characterized in that: When n=3, the silica sol solution includes a first silica sol solution, a second silica sol solution, and a third silica sol solution; The first silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the first silica sol solution is 10-30% and the pH is 4-6; The second silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the second silica sol solution is 31-41% and the pH is 4-6; The third silica sol solution is obtained by adjusting the pH of silica sol with ammonia water. The silica sol concentration of the third silica sol solution is 41-55%, and the pH is 4-6.

3. The integrated preparation method of gradient low dielectric high temperature resistant wave-transmitting material according to claim 2 is characterized in that: The preparation process of the porous quartz fiber ceramic body comprises the following steps: The quartz fiber and the alumina fiber are sheared respectively to obtain short fiber 1 and short fiber 2; Mix short fiber 1, short fiber 2, deionized water and additives in a ratio of (50-90): (10-40): (100-200): (10-15), stir and disperse for 60-120 minutes to obtain a quartz fiber ceramic slurry; Adding quartz fiber ceramic slurry into a molding mold, and then filtering and molding; Then, the product is dried and sintered at high temperature to obtain a porous quartz fiber ceramic body.

4. The integrated preparation method of gradient low dielectric high temperature resistant wave-transmitting material according to claim 3 is characterized in that: The additives include boron oxide and the like; the aspect ratio of the short fiber 1 is (100-1000):1, and the aspect ratio of the short fiber 2 is (100-500):

1.

5. The integrated preparation method of gradient low dielectric high temperature resistant wave-transmitting material according to claim 4 is characterized in that: The porous quartz fiber ceramic matrix includes a first porous quartz fiber ceramic matrix, a second porous quartz fiber ceramic matrix, and a third porous quartz fiber ceramic matrix; The porous quartz fiber ceramic body is placed in a vacuum container for vacuum treatment, the feed port at the bottom of the vacuum container is opened to siphon the first silica sol solution into the vacuum container, and the feed port at the bottom of the vacuum container is closed to continue vacuuming for 30-60 minutes; the porous quartz fiber ceramic body after impregnation is heated together with the container and the first silica sol solution, and the first silica sol solution is gelled; the porous quartz fiber ceramic body after gelation is dried at a drying temperature of (100-150)°C, and then high-temperature calcined at a calcination temperature of (600-800)°C to obtain a first porous quartz fiber ceramic matrix; the first silica sol solution is heated to a gelling temperature of (80-100)°C; The porous quartz fiber ceramic body is placed in a vacuum container for vacuum treatment, the feed port at the bottom of the vacuum container is opened to siphon the second silica sol solution into the vacuum container, and the feed port at the bottom of the vacuum container is closed to continue vacuuming for 30-60 minutes; the porous quartz fiber ceramic body after impregnation is heated together with the container and the second silica sol solution, and the second silica sol solution is gelled; the porous quartz fiber ceramic body after gelation is dried at a drying temperature of (100-150)°C, and then high-temperature calcined at a calcination temperature of (600-800)°C, and then high-temperature calcined to obtain a second porous quartz fiber ceramic matrix; The second silica sol solution is heated to a gel temperature of (80-100)°C; The porous quartz fiber ceramic body is placed in a vacuum container for vacuum treatment, the feed port at the bottom of the vacuum container is opened to siphon the third silica sol solution into the vacuum container, and the feed port at the bottom of the vacuum container is closed to continue vacuuming for 30-60 minutes; the porous quartz fiber ceramic body after impregnation is heated together with the container and the third silica sol solution, and the third silica sol solution is silica sol gelled; the porous quartz fiber ceramic body after gelling is dried at a drying temperature of (100-150)°C, and then high-temperature calcined at a calcination temperature of (600-800)°C, and then high-temperature calcined to obtain a third porous quartz fiber ceramic matrix; The third silica sol solution is heated to a gel temperature of (80-100)°C.

6. The integrated preparation method of gradient low dielectric high temperature resistant wave-transmitting material according to claim 2, characterized in that: The first porous quartz fiber ceramic substrate, the third porous quartz fiber ceramic substrate, and the third porous quartz fiber ceramic substrate are processed according to corresponding preset sizes to obtain a first porous quartz fiber ceramic sub-component, a second porous quartz fiber ceramic sub-component, and a third porous quartz fiber ceramic sub-component; The first porous quartz fiber ceramic sub-component has a thickness of 5-10 mm and a dielectric constant of 1.3-1.5; the second porous quartz fiber ceramic sub-component has a thickness of 30-40 mm and a dielectric constant of 1.5-1.6; the third porous quartz fiber ceramic sub-component has a thickness of 10-20 mm and a dielectric constant of 1.8-1.

9.

7. The integrated preparation method of gradient low dielectric high temperature resistant wave-transmitting material according to claim 5, characterized in that: The porous quartz fiber ceramic body includes a first porous quartz fiber ceramic body, a second porous quartz fiber ceramic body, and a third porous quartz fiber ceramic body; The ratio of short fiber 1, short fiber 2, deionized water and additives in the first porous quartz fiber ceramic body is (70-90): (10-20): (100-200): (10-15); The density of the first porous quartz fiber ceramic body is 0.297-0.505 g / cm 3 ; The ratio of short fiber 1, short fiber 2, deionized water and additive in the second porous quartz fiber ceramic body is (60-80): (20-30): (100-200): (10-15); The density of the second porous quartz fiber ceramic body is 0.595-0.65 g / cm 3 ; The ratio of short fiber 1, short fiber 2, deionized water and additives in the third porous quartz fiber ceramic body is (50-70): (30-40): (100-200): (10-15); The density of the third porous quartz fiber ceramic body is 0.81-0.95 g / cm 3 .

8. The integrated preparation method of gradient low dielectric high temperature resistant wave-transmitting material according to claim 1, characterized in that: The first porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, and the third porous quartz fiber ceramic sub-component are all arranged horizontally, and then the third porous quartz fiber ceramic sub-component, the first porous quartz fiber ceramic sub-component, and the second porous quartz fiber ceramic sub-component are sequentially bonded, connected, and fixed, and then sintered to obtain the gradient low-dielectric high-temperature resistant wave-transmitting material.

9. The integrated preparation method of gradient low dielectric high temperature resistant wave-transmitting material according to claim 1, characterized in that: When n=4, the silica sol solution includes a first silica sol solution, a second silica sol solution, a third silica sol solution, and a fourth silica sol solution; The first silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the first silica sol solution is 0-20% and the pH is 4-6; The second silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the second silica sol solution is 21-35%, and the pH is 4-6; The third silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the third silica sol solution is 36-45%, and the pH is 4-6; The fourth silica sol solution is obtained by adjusting the pH of silica sol with ammonia water, and the silica sol concentration of the fourth silica sol solution is 41-55%, and the pH is 4-6; and / or The porous quartz fiber ceramic body includes a first porous quartz fiber ceramic body, a second porous quartz fiber ceramic body, a third porous quartz fiber ceramic body, and a fourth porous quartz fiber ceramic body; The ratio of short fiber 1, short fiber 2, deionized water and additives in the first porous quartz fiber ceramic body is (80-90): (10-15): (100-200): (10-15); The density of the first porous quartz fiber ceramic body is 0.27-0.45 g / cm 3 ; The ratio of short fiber 1, short fiber 2, deionized water and additive in the second porous quartz fiber ceramic body is (70-80): (15-25): (100-200): (10-15); The density of the second porous quartz fiber ceramic body is 0.45-0.65 g / cm 3 ; The ratio of short fiber 1, short fiber 2, deionized water and additives in the third porous quartz fiber ceramic body is (60-70): (20-30): (100-200): (10-15); The density of the third porous quartz fiber ceramic body is 0.7-0.9; The ratio of short fiber 1, short fiber 2, deionized water and additives in the fourth porous quartz fiber ceramic body is (50-60): (30-40): (100-200): (10-15); The density of the fourth porous quartz fiber ceramic body is 0.85-0.95 g / cm 3 .

10. The integrated preparation method of gradient low dielectric high temperature resistant wave-transmitting material according to claim 9, characterized in that: The first porous quartz fiber ceramic substrate, the third porous quartz fiber ceramic substrate, the third porous quartz fiber ceramic substrate, and the fourth porous quartz fiber ceramic substrate are processed according to corresponding preset sizes to obtain a first porous quartz fiber ceramic sub-component, a second porous quartz fiber ceramic sub-component, a third porous quartz fiber ceramic sub-component, and a fourth porous quartz fiber ceramic sub-component; The first porous quartz fiber ceramic sub-component has a thickness of 45-50 mm and a dielectric constant of 1.3-1.4; the second porous quartz fiber ceramic sub-component has a thickness of 35-40 mm and a dielectric constant of 1.5-1.6; the third porous quartz fiber ceramic sub-component has a thickness of 25-30 mm and a dielectric constant of 1.7-1.8; the fourth porous quartz fiber ceramic sub-component has a thickness of 40-45 mm and a dielectric constant of 1.8-1.9; The first porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, and the third porous quartz fiber ceramic sub-component are all bent, and then the fourth porous quartz fiber ceramic sub-component, the third porous quartz fiber ceramic sub-component, the second porous quartz fiber ceramic sub-component, and the first porous quartz fiber ceramic sub-component are sequentially bonded, connected, and fixed, and then sintered to obtain the gradient low-dielectric high-temperature resistant wave-transmitting material.

Citation Information

Patent Citations

  • High-wave-transparent porous quartz / quartz ceramic-based composite material and preparation method thereof

    CN103724037A

  • Fiber-reinforced ceramic matrix wave-transparent material provided with FSS (frequency-selective surface) and preparation method

    CN109678476A

  • Multifunctional antenna protective cover and preparation method thereof

    CN116514560A

  • Lightweight high-temperature-resistant wave-transparent low-cost heat prevention and insulation silicon-based material and preparation method thereof

    CN118146016A